Investigation of chemical composition and cytotoxic activity of aerial parts of Ziziphora clinopodioides Lam. - F. Yousefbeyk (Research Journal of Pharmacognosy, 2016)
Background and objectives: Ziziphora clinopodioides is a perennial herb and grows widely in west and northwest of Iran. The aerial parts are used as appetizer, carminative and antiseptic as well as for the treatment of medical conditions such as high blood pressure, asthma hyperhidrosis, palpitation and insomnia Methods: The aerial parts of Ziziphora clinopodioides Lam. were extracted by ethanol (70%) and fractionated by n-hexane. The n-hexane fraction was analyzed by GC and GC/MS. This fraction and the total extract were further investigated for in vitro cytotoxic activity against HT-29 (colon carcinoma), K-562 (leukemia), T-47D (breast ductal carcinoma) and NIH-3T3 (Swiss mouse embryo fibroblast) cells using MTT assay. Results:  Nineteen compounds were identified by GC/MS. The main constituents of the n-hexane fraction were pulegone (24.35%), menthol (14%) and menthone (9.61%). The results of cytotoxicity evaluation showed that the n-hexane fraction strongly exhibited cytotoxic activity against T-47D and K-562 cells with IC50 value of 77.41±12.89 and 80±2.56 μg/mL. The total extract did not show considerable activity against any of the cell lines in comparison to the n-hexane fraction. Conclusion: The presence of compounds such as pulegone, menthol and menthone could explain the cytotoxic activity of the n-hexane fraction of Z. clinopodioides Lam on K-562, T-47D and HT-29 cell lines.